TILLING in European Rice: Hunting Mutations for Crop Improvement. Issue 6 (1st November 2013) - Casella, Laura; Greco, Raffaella; Bruschi, Gianluca; Wozniak, Barbara; Dreni, Ludovico; Kater, Martin; Cavigiolo, Stefano; Lupotto, Elisabetta; Piffanelli, Pietro
ABSTRACT: Targeting induced local lesions in genomes (TILLING) is a powerful technique that exploits variation induced by classical mutagenesis for gene discovery and functional studies as well as crop improvement. Here we describe the development and validation of the first rice ( Oryza sativa L.) TILLING platform of a European temperate japonica accession. A total of 1860 M2 ethyl methane sulfonate (EMS)‐mutagenized lines were generated in the variety 'Volano', one of the most widely cultivated European rice varieties representative of the traditional Italian high quality rice. The validation of the TILLING population was performed by screening the M2 lines for variation in four target genes of relevance for the improvement of Volano ( SD1, Hd1, SNAC1, and BADH2, involved in determining plant height, flowering time, drought tolerance, and aroma, respectively). Two independent mutations identified in the Green Revolution gene SD1 ( semidwarf 1 ) were demonstrated to have a significant phenotypic effect, resulting in semidwarf progenies with an average height reduction of 21% in the plants carrying the mutant allele in the homozygous state. The density of one mutation every 373 kb estimated in the Volano TILLING population was comparable to that previously obtained in rice EMS‐mutagenized populations and confirmed the effectiveness of this approach for targeted improvement of European temperate rice germplasm. Besides the validation of the TILLING platform, this work also provides genetic material that can be directly exploited for the improvement of the Volano variety.